The Influence of Work Environment on Employee Performance: The Mediating Role of Job Satisfaction - Harendra K. C.; Purna Man Shrestha (MASI Mandiri Edukasi, 2026)
Employees are the cornerstone of the organization. This research explores the relationship between the work environment and employee performance within cooperative societies in Nepal’s Karnali Province, specifically examining the mediating role of job satisfaction. Using a quantitative research design, data were collected from 404 cooperative employees via convenience sampling. The conceptual framework, grounded in Social Exchange Theory and Job Demands-Resources Theory, was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.1.1.6. The empirical results reveal a significant positive correlation between the workplace environment and employee performance. Furthermore, the work environment was found to be a strong predictor of job satisfaction. The analysis confirms that job satisfaction serves as a partial mediator; essentially, a supportive physical, psychological, and social environment drives productivity both directly and indirectly by fostering higher satisfaction levels among personnel. These insights provide actionable guidance for cooperative managers and HR practitioners, highlighting cultivating a favorable work climate as a strategic lever for organizational success. By investigating a relatively overlooked regional and sector-specific context, this study addresses a notable gap in the empirical literature concerning the Nepalese cooperative industry and contributes to the broader understanding of organizational behavior in developing nations.